The economic impact of foot and mouth disease control and eradication in the Philippines - Randolph, Thomas F.; Perry, Brian D.; Benigno, C.C.; Santos , I.J.; Agbayani, A.L.; Coleman, P.; Webb, R.; Gleeson, L.J. (World Organisation for Animal Health, 2002)
The authors evaluate the impact of foot and mouth disease (FMD) and control of the disease in the Philippines using cost-benefit analysis. A scenario in which FMD control is maintained at recent levels with continued presence of the disease is compared to scenarios in which a publicly funded programme achieves eradication by 2005 (current policy objective), 2007 and 2010. Under varying assumptions regarding the development of exports of livestock products following eradication, estimated benefit-cost ratios for the investment in eradication range from 1.6 (2010, no exports) to 12.0 (2005, export of 5,000 tonnes each of low-value and high-value livestock products annually), indicating eradication to be an economically viable investment. The commercial swine sector is estimated to capture 84% of the benefits generated by the public investment in eradication, versus 4% by backyard swine producers. The implications of these results within the context of regional efforts to control FMD in South-East Asia are explored.